2010
DOI: 10.1007/s12649-010-9028-4
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration and Characterization of Traced Polypropylene with Rare Earth Oxides for Automatic Identification and Sorting of End-of-Life Plastics

Abstract: The rare earth oxides can be used as tracers forthe identification of polymer materials. This study focusedon the detection of these particles and their effects on themechanical and thermal properties of polypropylene (PP).A new method was carried out to increase the sortingselectivity of PP during end of life recycling process and toimprove the efficiency of sorting and its high speed identification.The tests were realized in a test system devicewhich allows the collection of static measurements of thesamples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In previous work [2], it has been shown that the addition of 1 wt % of Nd 2 O 3 and Gd 2 O 3 leads to a slight increase of the Young's modulus and a slight decrease of the yield stress. Regarding the tensile tests, the most important effect of these rare earth oxides was observed on the elongation at break.…”
Section: Effect Of Tracers On Mechanical Propertiesmentioning
confidence: 93%
See 2 more Smart Citations
“…In previous work [2], it has been shown that the addition of 1 wt % of Nd 2 O 3 and Gd 2 O 3 leads to a slight increase of the Young's modulus and a slight decrease of the yield stress. Regarding the tensile tests, the most important effect of these rare earth oxides was observed on the elongation at break.…”
Section: Effect Of Tracers On Mechanical Propertiesmentioning
confidence: 93%
“…Tracers consist of systems formed by one or several substances dispersed into a material with the aim of adding a selective property to it and improving its identification. In recent works [1,2], an X-ray fluorescence (XRF) detection system based on the use of tracers for the identification of polymer materials was reported by the authors. This system was developed with the objective of having an economical, efficient and automatic sorting of plastic wastes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bezati et al [11][12][13][14] have shown that the X-ray fluorescence allows the detection of few tracers, while the magnetic detection is applied for the detection of only one tracer. Furthermore, the X-ray fluorescence detection which is a volume detection, can be a reliable method for high speed identification and sorting of black plastics into different families and grades.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] In particular, the use of identification (ID) taggants as smart additives could enable automatic identification, tracking, and tracing of materials, thus aiding the implementation of sustainable concepts, such as Circular Economy. [ 2–6 ] Additionally, developments in the digitalization of manufacturing could be fostered by the realization of the Internet of Things, thanks to programmable ID taggants. [ 7–9 ] Moreover, ID taggants could contribute to the establishment of transparent global trading networks and prevent product counterfeiting, thereby improving quality assurance.…”
Section: Introductionmentioning
confidence: 99%